2021
DOI: 10.17582/journal.pjar/2021/34.2.300.308
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Sequestration and Biomass Assessment of Mott Grass (Pennisetum purpureum), in three Growth Stages in Barani Areas of Pothwar, Pakistan

Abstract: Alternative renewable energy is getting progress in current era keeping in view of energy insecurity in the coming years and the ever increasing threat of environmental and social health due to the use of fossil fuel. Lingo-cellulosic biomass has seen getting fame as bioenergy crops in maintaining food security alongside fulfilling energy demands. Napier grass (Pennisetum purpureum) has turn out the promising nutritious forage to the livestock on the sustainable basis, feedstock for biofuel and also has proven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…This has a negative impact on primary biomass production, which further affects animal productivity as discussed in (Wullschleger et al 2010). In the Pothwar region, winter rainfall is an important factor in controlling the composition and new growth of plant communities while summer rainfall is important for increasing the biomass production of existing plant species needed to sustain animals when other fodders are scarce (Shehzadi et al 2021). It has been observed that reductions in winter rainfall reduce germination and then establishment of plants, whereas summer drought is responsible for reducing grassland productivity (Bittencourt et al 2013).…”
Section: Aboveground Vegetation Biomass Canopy Cover and Nutritional ...mentioning
confidence: 99%
“…This has a negative impact on primary biomass production, which further affects animal productivity as discussed in (Wullschleger et al 2010). In the Pothwar region, winter rainfall is an important factor in controlling the composition and new growth of plant communities while summer rainfall is important for increasing the biomass production of existing plant species needed to sustain animals when other fodders are scarce (Shehzadi et al 2021). It has been observed that reductions in winter rainfall reduce germination and then establishment of plants, whereas summer drought is responsible for reducing grassland productivity (Bittencourt et al 2013).…”
Section: Aboveground Vegetation Biomass Canopy Cover and Nutritional ...mentioning
confidence: 99%